Law students and social distance towards migrants and some other relevant groups in Croatia - Gregurović, Margareta (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2022)
Increased migration and the effects of the 2015/16 European migration/refugee crisis are reflected in changes in the attitudes towards migrants and members of certain religions. Law students, who are thought to come into contact with the issue of migration in their work, are of greater concern. This paper presents the results of a survey conducted in 2019 among 1st and 4th year law students at four law schools in Croatia. The study aims to determine how close a relationship (on Bogardus’ social distance scale) law students would achieve with the various types of migrants, Roma, and members of different religions. The results show that law students are likely to have the closest relationship with immigrants from North America and Western European countries and express the greatest average distance towards asylum seekers. They associate the greatest social closeness with Catholics. The analyses of the effects of sociodemographic characteristics, contextual indicators, and value orientations and attitudes on social distance imply that nationalism has the strongest effect on all groups.
Keywords: Hrvaška; migranti; socialna distanca; študenti prava; verske skupine